Extraction and antitumor activity evaluation of small molecular weight collagen peptides from Chinese giant salamander (Andrias davidianus) skin - Ting Ye; Xiang Zhang; Jiahui Li; Shumao He; Jianlin Luo; Jianguo Lu; Can Li (Food Science of Animal Products)
The skin of the Chinese giant salamander (Andrias davidianus) is a rich source of collagen. However, current research indicates limited efficiency and activity in collagen protease hydrolysis from this source. Further enzymatic hydrolysis to produce small molecular weight active peptides and their antitumor potential remain underexplored. This study employed a two-step enzymatic hydrolysis method to prepare small molecular weight collagen peptides (SMWCPs), followed by ultrafiltration separation. The extraction process was optimized using single-factor and response surface methodology. The amino acid composition of SMWCPs was analyzed, and their antitumor activity was assessed in vitro through cell migration, cell cycle, and apoptosis assays. Results revealed a negative correlation between collagen peptide molecular weight and antitumor activity, with optimal antitumor activity observed for peptides with a molecular weight of 300–1 000 Da (neutral protease hydrolyzed Chinese giant salamander skin collagen peptides (NP-GSKCP)). Optimal extraction conditions were: enzyme dosage 8 000 U/g, enzymatic hydrolysis temperature 52.6 °C, enzymatic hydrolysis pH 7.1, and enzymatic hydrolysis time 4.3 h, yielding 87.82% NP-GSKCP-IV. Notably, NP-GSKCP-IV contained 55.31% hydrophobic amino acids. Treatment of A549 cells with 5 mg/mL NP-GSKCP-IV significantly altered cell morphology, inhibited migration, arrested the cell cycle at G0/G1 phase, and induced early apoptosis. This study contributes to the development of efficient extraction techniques for antitumor active ingredients from Chinese giant salamander skin and informs the potential development of medicinal functional foods.